2009
DOI: 10.4103/0971-4065.57106
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation in kidney lipid metabolic profiles in diabetic rats with reference to alcoholic oxidative stress

Abstract: Diabetes is a major threat to global public health, and the number of diabetic patients is rapidly increasing worldwide. Evidence suggests that oxidative stress is involved in the pathophysiology of diabetic complications and alcoholic diseases. The aim of this study is to find out the impact of alcohol on lipid metabolic profiles in kidney tissue under streptozotocin induced diabetic condition. No study has been reported so far on the effect of alcohol on diabetic condition and also with reference to lipid me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…De-Vries et al, [19] stated that in vivo and in vitro experiments, there was an association between intrarenal accumulation of lipid components and renal injury. In addition, Shanmugam et al, [20] reported fatty infiltration in renal tissue of diabetic rat and attributed this to oxidative stress that led to free radicals formation and abnormal fat metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…De-Vries et al, [19] stated that in vivo and in vitro experiments, there was an association between intrarenal accumulation of lipid components and renal injury. In addition, Shanmugam et al, [20] reported fatty infiltration in renal tissue of diabetic rat and attributed this to oxidative stress that led to free radicals formation and abnormal fat metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological examination of the kidney tissue in diabetic control group showed severe loss of the glomerular capillaries, tubular cell degeneration and presence of hyaline casts (Figure 5). These changes observed may be attributed to glomerular hyper filtration, disturbed glucose metabolism and oxidative tissue damage [50,51]. The diabetic group treated with vindoline showed gradual improvement in the structure of the glomerulus and the renal tubules although the renal tubules still had hyaline casts within their lumen.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, hepatic TBARS level was increased in the HFD group. It is reported that hyperglycemia and hypertriglyceridemia evoke the hepatic lipid peroxidation due to β -oxidation overload that is characterized by high TBARS level [ 42 ]. Also level of GSH, GST, and NO are elevated in HFD group.…”
Section: Discussionmentioning
confidence: 99%